IoT-Based Motorcycle Hydraulic Brake Condition Monitoring System with Real-Time Website Integration - Aufil Ahda Elok Hijriyani; Raka Pratindy; Faris Humami; Rifano (Academic Bright Collaboration, 2026)
Purpose - Brake failure on motorcycles, particularly on downhill roads, remains a critical safety hazard driven by thermal overheating, fluid degradation, and fluid-loss conditions that conventional single-parameter monitoring systems fail to detect comprehensively. This study successfully developed and preliminarily evaluated an IoT-based multi-sensor monitoring system for real-time detection of hydraulic disc brake conditions on motorcycles using a Research and Development approach. Method - The prototype integrates a Thermocouple Type K, a capacitive moisture sensor, a Level Sensor K-0135, and a GPS BN-220 connected to an ESP32 DevKit V1 microcontroller with MySQL database and Laravel 12 web dashboard integration. Validation encompassed laboratory calibration, 40 scenario classification tests, 50 trial response time measurements, and field testing on flat and downhill roads. Findings -All sensors achieved high accuracy, with thermocouple accuracy of 98.9%, moisture sensor 97.4%, level sensor 98.82%, and GPS speed 97.3% with 100% rule-based output conformity across all 40 predefined scenarios and a mean response time of 0.9314 seconds. Field classification across 3,201 time-series readings yielded an overall classification consistency of 93.22%, with perfect recall for CRITICAL and WARNING states based on predefined threshold rules. Brake pad temperature escalated from 35°C to 134°C on downhill roads, preliminarily supporting the 120°C threshold as an early warning boundary, consistent with documented brake fluid thermal degradation characteristics. Thermocouple reliability decreased to 67.7% under worst-case vibration due to short-circuit interference, representing a critical limitation affecting system reliability under real-world conditions, while dashboard operation remains dependent on stable internet connectivity. Research Implications - This study extends prior single-parameter approaches through a three-tier classification framework (NORMAL–WARNING–CRITICAL). Originality - with the primary contribution lying in the repositioning of the thermocouple from the reservoir to the brake pad surface, enabling more proximal thermal monitoring at the friction interface under the tested conditions.